The association between nation-level social and economic indices and suicide rates: A pilot study - Rajkumar, Ravi Philip (Frontiers in Sociology, 2023)
Ever since the pioneering work of Emile Durkheim, it has been known that regional or national suicide rates can be influenced by a variety of social and economic factors. Recent research has found a robust association between two country-level economic indices – gross national product and unemployment rate – and suicide rates, particularly in men. However, the association between other country-level social indices – such as measures of social integration, inequality, environmental preservation and political freedom – and suicide rates has not been studied at the cross-national level. In the current study, national suicide rates for men and women were examined in relation to seven indices measuring subjective well-being, sustainable development, type of political regime, economic and gender inequality, and social capital. It was found that the Happy Planet Index, a composite measure of subjective well-being and sustainable development, was negatively associated with suicide rates independent of gender, and even after adjusting for possible confounding factors. Economic inequality was associated with suicide in men, and social capital was associated with suicide in women. Moreover, the strength and direction of the associations observed between socioeconomic indices and suicide varied across income groups. These results highlight the need for a closer evaluation of the link between large-scale (“macro”) social factors and individual (“micro”) psychological factors, as well as the importance of integrating these factors into suicide prevention programmes at the national level.